The Growing Complexity of the Academic Enterprise in Europe: A Panoramic View - Kwiek, Marek (Peter Lang, 2012)
The increasingly complicated picture of the academic enterprise in Europe is due to several general factors: globalization and Europeanization, educational expansion and the massification of higher education, the economic crisis and public sector reforms, and the knowledge-driven economic competitiveness of nations and regions. Some factors, like expansion and massification, have exerted their influence over a few decades; others, like the economic crisis, for a few years. They can be put under four more general categories of external pressure exerted on higher education: economic (financial), political (ideological), social, and demographic. The factors generating change in national higher education policies and in national higher education systems have been multilayered, interrelated and often common throughout the continent. The growing complexity of the academic enterprise today is also due to the fact that higher education systems in Europe have been under powerful reform pressures.1 2 Reforms increasingly today, and throughout the European continent, lead to further reforms rather than to reformed higher education systems. Higher education has changed substantially in most European economies in the last two or three decades but it is still expected by national and European-level policymakers to change even more. There are a number of broad features that add to the complexity of the academic enterprise. In general, they include the acceleration of national, European and global discussions; permanent renegotiations of the state/university relationships; universities functioning under permanent conditions of adapting to changing environmental settings; renegotiations of the general social contract providing the basis for the post-war welfare state and its public services; the tremendous scale of operations of and funding for universities; the divergence between global, supranational, European and often national reform discourses and academic discourses about the future of the university; and the link between arguments about private goods/ private benefits from higher education and arguments about public subsidization of higher education.
Keywords: European higher education; complexity; university governance; university funding; public sector; reforms; public policy; higher education research; globalization; Europeanization; comparative education; higher education policy; educational policy; Bologna Process; European integration; university missions; privatization; public goods; marketization